Effects of Different Corn Protein Sources and Level on Nursery Pig Growth Performance and Feed Efficiency - Z. X. Rao; J. C. Woodworth; M. D. Tokach; S. S. Dritz; J. M. DeRouchey; R. D. Goodband; H. I. Calderón; K. Mertz (Kansas Agricultural Experiment Station Research Reports, 2020)
This experiment was conducted to determine the effects of 3 corn protein sources added at the expense of other specialty protein sources or corn on nursery pig growth performance and feed efficiency (F/G), and economic return. A total of 315 pigs (241 × 600; DNA, Columbus, NE; initially 12.1 lb) were used in a 35-d growth trial. There were 5 pigs per pen and 9 replicates per treatment. The treatments were structured as a randomized complete block design and arranged in a 3×2+1 factorial with main effects of corn protein source (CP1, CP2, and CP3; Cargill Inc., Blair, NE) and level (5 or 10%) plus a control diet. Treatment diets were fed in 2 phases (phase 1: d 0 to 7; phase 2: d 7 to 21) with a common diet fed from d 21 to 35. In phase 1, protein sources were added at the expense of fish meal in the 5% inclusion diets and replaced both fish meal and enzymatically treated soybean meal (HP300) for the 10% inclusion diets. In phase 2, protein sources were added at the expense of fish meal in the 5% inclusion diets, and both fish meal and corn in the 10% inclusion diets. All diets were fed in pellet form throughout the trial. In the treatment period (d 0 to 21), increasing corn protein sources decreased (linear, P<0.05) average daily gain (ADG) and average daily feed intake (ADFI). Feed efficiency worsened (linear, P<0.05) when pigs were fed increasing CP1 or CP2 and tended to worsen (linear, P<0.10) when fed increasing CP3. The growth performance was poorest when the 10% level of the corn protein sources were fed with the 5% level of CP2 or CP3, eliciting similar performance to the control-fed pigs. Pigs fed CP1 had decreased (P<0.05) ADG and ADFI compared to those fed CP2 or CP3. The poorer growth performance of pigs fed CP1 resulted in lower d 21 body weight (BW) (P<0.05) compared to those fed CP2 or CP3. There was no evidence of any difference between pigs fed CP2 and CP3 on all growth performance criteria throughout the treatment period. In the common period (d 21 to 35), compensatory growth and feed intake were observed, but final BW was still lower when pigs were fed diets with any of the corn protein sources compared to pigs fed the control diet. In summary, increasing amounts of these three corn protein sources, at the expense of specialty protein sources such as fish meal, decreased growth performance in nursery pigs; however, the magnitude of the impact differed between corn protein sources and level with 5% inclusion of CP2 and CP3 eliciting similar performance to the control. Additional research should be conducted to further compare corn protein sources and help identify why some sources influence performance differently than others.
Keywords: corn protein; growth; nursery; pigs